Review of droplet entrainment in annular flow: Characterization of the entrained droplets. (March 2015) - Berna, C.; Escrivá, A.; Muñoz-Cobo, J.L.; Herranz, L.E.
Abstract: Annular flow is characterized by a thin liquid film flowing on the pipe wall and a high velocity gas core flowing in its center, which normally carries liquid droplets. This review presents and analyzes most of the extensive literature existing on the annular two-phase flow, focusing specifically on the analysis of the main phenomena that are involved. In particular, the paper focuses on the study of the liquid droplets that are entrained by the gas stream from the gas–liquid interface, due to the strong influence that these droplets exert in many important parameters of both, flow and heat transfer processes. Consequently, it is important to be able to know the maximum amount of information about them, in order to characterize droplets' size and velocity, and to determine the amount of them that are entrained into the gas stream and, finally, apply this knowledge in all processes in which annular flow is involved. This review analyzes most of the extensive literature on droplets, specifically analyzes its main characteristics once they have been formed, such as its sizes, speeds and total amount. A vast amount of data has been found in the open literature and collected here. Their analysis leads to two major observations: their huge scattering and the existence of remaining knowledge gaps. Some of the experimental data have been also used to derive new correlations on variables as important as amount and size of entrained droplets. Highlights: Review of the most recent literature on annular two-phase flow. Emphasize all variables and processes occurring in the gas phase. Show the existing scattering found when expressions are compared to each other. Highlight the gaps of knowledge still existing. Propose new correlations for key variables: droplet sizes and entrained fraction.